Sex Identification of Four Penguin Species Using Locus‐Specific PCR. Issue 3 (2nd March 2012) - Zhang, Peijun; Han, Jiabo; Liu, Quansheng; Zhang, Junxin; Zhang, Xianfeng
<x xml:space="preserve">Abstract</x> Traditional methods for sex identification are not applicable to sexually monomorphic species, leading to difficulties in the management of their breeding programs. To identify sex in sexually monomorphic birds, molecular methods have been established. Two established primer pairs (2550F/2718R and p8/p2) amplify the CHD1 gene region from both the Z and W chromosomes. Here, we evaluated the use of these primers for sex identification in four sexually monomorphic penguin species: king penguins (Aptenodytes patagonicus), rockhopper penguins (Eudyptes chrysocome), gentoo penguins (Pygoscelis papua), and Magellanic penguins (Spheniscus magellanicus). For all species except rockhopper penguins, primer pair 2550F/2718R resulted in two distinct CHD1Z and CHD1W PCR bands, allowing for sex identification. For rockhopper penguins, only primer pair p8/p2 yielded different CHD1Z and CHD1W bands, which were faint and similar in size making them difficult to distinguish. As a result, we designed a new primer pair (PL/PR) that efficiently determined the gender of individuals from all four penguin species. Sequencing of the PCR products confirmed that they were from the CHD1 gene region. Primer pair PL/PR can be evaluated for use in sexing other penguin species, which will be crucial for the management of new penguin breeding programs. Zoo Biol 32:257–261, 2013. © 2012 Wiley Periodicals, Inc.